Implications of Recent Research for the Preschool and Kindergarten Curriculum - Katz, Lilian G. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
Summarized are implications of recent research on children's development and learning for the curriculum in early childhood programs. Contents focus on the development of language, dispositions, social competence, and intellect. Taken together, the research suggests that children attending preschool and kindergarten classes should frequently be provided with opportunities for involvement in projects. A project is defined as a group undertaking, usually concerning a specific theme or topic, which requires various kinds of work over a period of several days or weeks. Concluding remarks identify three basic kinds of projects and three phases of project work. A three-page list of references concludes the document. (RH)
ERIC Note: Document contains light, dot matrix print.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Emotional Development; Individual Development; Interpersonal Competence; Kindergarten; Language Acquisition; Preschool Curriculum; Preschool Education; Student Interests; Student Projects; Teaching Methods; Research Results; Opinion Papers